Development of wood-lime boards as building materials improving thermal and moisture performance based on hygrothermal behavior evaluation. (20th April 2019) - Park, Ji Hun; Kang, Yujin; Lee, Jongki; Chang, Seong Jin; Wi, Seunghwan; Kim, Sumin
Highlights: Wood-based materials containing lime binder were prepared. Analysis of wood-based materials is carried out depending on ISO and ASTM standard. Wood-based materials using lime binder improves heat and moisture performance. Total water content and mold growth risk of wood-lime boards were decreased. Wood-based materials using lime binder were applicable as building materials. Abstract: Currently, wood is attracting attention as an eco-friendly building material that has advantages such as high insulation performance and low CO2 emission. However, it is vulnerable to moisture. Therefore, the objective of this study was to develop wood-lime boards using lime as resins that is known to be excellent in moisture control. Hygrothermal behaviors of such wood-lime boards were then analyzed to confirm their applicability as building materials. Results of hygrothermal behavior analysis revealed that they had higher insulation performance and higher water vapor resistance factor. Simulation analysis results also indicated that both total water content and mold growth risk were reduced when wood-lime boards were used in comparison with existing layers. Therefore, wood-lime boards were applicable as building materials.